Electronic phase diagram of oxygen-deficient SmNiO3−δ epitaxial thin films. (16th May 2017) - Chen, Bin-Jie; Sun, Yan; Yang, Nan; Zhong, Ni; Zhang, Yuan-Yuan; Bai, Wei; Sun, Lin; Tang, Xiao-Dong; Yang, Ping-Xiong; Xiang, Ping-Hua; Duan, Chun-Gang
Abstract: Epitaxial SmNiO3− δ thin films were fabricated under various oxygen partial pressures ( P O 2 ) on (0 0 1)-oriented LaAlO3 substrates by using the pulsed laser deposition method. Continuous control of the metal–insulator transition temperature ( T MI ) from 350 K to 85 K was achieved by varying P O 2 from 26 Pa to 0.5 Pa. The reduction of T MI can be attributed to the straightening-out of the out-of-plane Ni–O–Ni bond angle due to the elongation of unit cell volume with decreasing P O 2 . When P O 2 > 3 Pa, resistivity anomalies around 200 K are observed in the insulating phase of strained SmNiO3− δ films, suggesting the onset of antiferromagnetic ordering of the Ni sublattices. An electronic phase diagram of the oxygen-deficient SmNiO3− δ films has been established in this work based on the results of the transport measurements.